2012
DOI: 10.3738/na.v4i2.796
|View full text |Cite
|
Sign up to set email alerts
|

Efeito Do Implante Intravaginal De Progesterona Sobre a Ciclicidade De Éguas Em Anestro Da Raça Quarto De Milha

Abstract: O presente estudo teve como objetivo acompanhar a dinâmica folicular de dez éguas submetidas à inserção do dispositivo de liberação lenta de progesterona e, verificar se este procedimento antecipa o início da ciclicidade ovariana em éguas em anestro. Para isso, foram colhidos dados do uso de implante intravaginal de progesterona em éguas que se encontravam em anestro. Após dez dias da colocação do implante, o mesmo foi removido e administrado 0,25 mg de prostaglandina F2α por via intramuscular. As éguas foram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(9 reference statements)
1
1
0
Order By: Relevance
“…The percentage of embryo recovery observed in the CG (52.94 %) is concordant with literature data, which show that it can vary from 40 to 80 % (Fleury et al 2001, Squires et al 2003, Vazquez et al 2010, Gomes et al 2014. Some factors, such as the professional's experience and variations in environmental temperature, influence the ERR in mares (Oliveira et al 2015, Cuervo-Arango et al 2018 (Oliveira Filho et al 2012) was probably more promising because the diameter of the preovulatory follicle was larger. In addition, the animal breed used (Quarter Horse) has been bred specifically for reproduction, a different geographical location was used, with different device timing permanence (10 days), ovulation inducers and seasonality, all of which could be influencing factors among the animals surveyed.…”
Section: Discussionsupporting
confidence: 84%
“…The percentage of embryo recovery observed in the CG (52.94 %) is concordant with literature data, which show that it can vary from 40 to 80 % (Fleury et al 2001, Squires et al 2003, Vazquez et al 2010, Gomes et al 2014. Some factors, such as the professional's experience and variations in environmental temperature, influence the ERR in mares (Oliveira et al 2015, Cuervo-Arango et al 2018 (Oliveira Filho et al 2012) was probably more promising because the diameter of the preovulatory follicle was larger. In addition, the animal breed used (Quarter Horse) has been bred specifically for reproduction, a different geographical location was used, with different device timing permanence (10 days), ovulation inducers and seasonality, all of which could be influencing factors among the animals surveyed.…”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, Schutzer (2012) reported that 46% (7/15) of the mares ovulated within 60 days after starting treatment with P4 implants, and only 13.46% (2/15) ovulated in the control group. Results that showed the superiority of ovulation rate in mares submitted to treatment with P4 implant were also demonstrated by De Oliveira Filho et al (2012), who reported that 80% (8/10) of the mares ovulated after treatment against 20% (2/10) of the mares group without P4.…”
Section: G1 G2mentioning
confidence: 64%